2023
DOI: 10.15407/oncology.2023.01.039
|View full text |Cite
|
Sign up to set email alerts
|

The Value of the Expression of K-Ras and Dna-Status in the Progression of Endometrioid Endometrial Carcinoma in Patients With Early Stages of Tumor Process

Abstract: Summary. Aim: evaluation of DNA ploidy and K-RAS oncoprotein expression in endometrioid endometrial carcinoma (EEC) to determine the metastatic potential of patients with an initial stage of the malignant process. Objects and methods: the study was conducted on samples of postoperative material of 54 patients with EEC stage I according to FIGO (average age: 60.4 years; part from 38 to 72 years). Clinical, morphological, immunohistochemical, flow cytometry, and statistical methods were used for the research. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Laser flow cytometry was used to determine the proliferation index (PI, %, the number of cells in S+G 2 /M phases of the mitotic cycle) [18]. The study was performed on an EPICSXL flow cytometer (Beck man Coulter, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Laser flow cytometry was used to determine the proliferation index (PI, %, the number of cells in S+G 2 /M phases of the mitotic cycle) [18]. The study was performed on an EPICSXL flow cytometer (Beck man Coulter, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The change in miRNA expression compared to the control was calculated �y the formulas of � -ΔCt . The proliferative activity of the studied endometrial carcinoma was determined �y the proliferation index �PI� %�� using the method of flow cytofluorometry [5]. The study was performed on a flow cytofluorimeter EPICS-XL �Beckman Coulter� USA�.…”
Section: Methodsmentioning
confidence: 99%
“…Today� according to the recommendations of the European Society of Medical Oncologists� ECE is divided into four molecular su�types� which are characterized �y a certain range of mutations and gene expression profiles� which require different treatment strategies [���]. In our previous studies� it was shown that aggressive ECE forms are characterized �y higher expression of cyclins E and �1� transcription factor E�F1 and aneuploidy than tumors with low potential for malignancy [5]. The association of varia�ility of the morphological ECE phenotype with changes in the expression of the markers of epithelial-mesenchymal transition �EMT� was revealed and their relation to possi�le pathways of tumor cell migration was su�stantiated [6].…”
mentioning
confidence: 96%
“…Current model of EC pathogenesis is viewed from the position of state-of-the-art data, obtained from the studies of molecular-biological specificities of tumors. These studies helped to determine the biological heterogeneity of ECE defining the clinical course and being responsible for the differences in the aggressiveness of the tumor process [9][10][11][12][13][14][15][16].…”
mentioning
confidence: 99%
“…The existing data of scientific literature and the results of our research have demonstrated that the tumor progression in ECE is associated with unfavorable clinical course and the impaired expression of some suppressor genes, oncogenes, cellular cycle regulators, and markers of epithelial-mesenchymal transition (EMT) [6,[14][15][16]18]. However, it has not yet been clear how to discern ECE with high potential of malignancy.…”
mentioning
confidence: 99%